Anatomical Relationship of the Middle Cranial Fossa Dura to Surface Landmarks of the Temporal Bone. Issue 9 (October 2017) - Alhussaini, Mohamed A.; Mattingly, Jameson K.; Cass, Stephen P.
Abstract : Hypothesis: The suprameatal crest and temporal line provides a reliable landmark to the middle fossa dura. Background: Surface anatomy of the temporal bone is used to guide mastoid surgery, but studies investigating these landmarks are limited. The aim of this study was to examine the anatomical relationship of the middle fossa dura to the temporal line. Methods: Thirty-two fresh hemicephalic temporal bones were prepared by drawing four lines along the mastoid including the suprameatal crest and temporal line (line 2), one line 5 mm superior to line 2 (line 1), and one 5 mm inferior to line 2 (line 3), and at Reid's base line (line 4). Four points were marked along these lines anterior to posterior 3 mm apart. A 1 mm bur was used to drill perpendicular to these points to examine the relationship to the middle fossa dura. Results: The dura was found inferior to line 2 in 6.3% at point 1, 6.3% at point 2, 9.4% at point 3, and 18.8% at point 4. The dura in line 1 was found inferior to point 1 in 52.1%, point 2 in 46.9%, point 3 in 56.3%, and point 4 in 62.5%. Only one specimen (3.1%) had dura lying inferior to line 3. No specimens were inferior line 4 at any point. Conclusion: The dura of the middle fossa lies superior the temporal line in >80% of specimens and at least 5 mm superior in nearly half. This indicates the temporal line or a line slightly inferior to this is reliably inferior the middle fossa dura.